What came before he shot her - George, Elizabeth, 1949-. (Harper fiction, 2008)
A kind and well-loved woman was brutally and inexplicably murdered. The pregnant wife of a respected police inspector, her death has left Scotland Yard shocked and searching for answers. Perhaps most horrifying of all, the trigger of the weapon that killed her was apparently pulled by a stranger . . . a twelve-year-old boy.The anatomy of a murder, the story of a family in crisis, What Came Before He Shot Her is a powerful, emotional novel full of deep psychological insights, a novel that only the incomparable Elizabeth George could write.